Integration of Philosophy of Science in Adaptive Language Learning Methods in Multicultural Classrooms - Rumaisya Fadil, As-syfa; M. Zaim; Effendi Thahar, Harris (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
In the increasingly complex context of multicultural education, it is important for educators to understand how different perspectives can be integrated into learning methods to make them relevant and inclusive. One approach that can support this is to utilize philosophy of science, which provides a critical foundation for evaluating and developing learning strategies. Therefore, it is important to conduct an in-depth study on how philosophy of science can be effectively applied in culturally diverse educational environments. This study aims to examine the integration of philosophy of science in adaptive language learning methods in multicultural classrooms. Through a descriptive qualitative approach, the study explored the challenges and strategies faced by 10 educators with experience in multicultural environments. Key findings included challenges in understanding students' cultural diversity, limited resources, as well as difficulties linking theory with practice. Educators reported a lack of relevant teaching materials and adequate training, potentially hindering learning effectiveness. This research recommends the development of inclusive resources and improved professional training to create learning environments that are more adaptive and responsive to student diversity. These results are expected to contribute to improving the quality of learning in multicultural classrooms